From Rivals to Partners: Constructing the Sino-Indonesian Strategic Partnership - Priyandita, Gatra (UI Scholars Hub, 2019)
This study is an inquiry into the use of strategic partnerships as an instrument of diplomacy in Indonesia. Strategic partnerships have become a key fixture of Indonesia’s omnidirectional foreign policy in the post-Suharto era. However, the rationale behind the formation of strategic partnerships for Indonesia’s strategic interests, as well as the process behind its formation, remain understudied. This paper seeks to fill this gap in the literature by examining how Indonesia utilizes its strategic partnership to engage China. Using Wilkins’ analytical framework for the study of strategic partnerships, this study finds that Indonesian policymakers have used strategic partnerships as instruments to create multiple channels of communication for the purposes of economic pragmatism and the overarching goal of socializing the target state into accepting Indonesia’s vision of the international order. The case study on China indicates that strategic partnerships have only been partially successful in helping Indonesia deliver its goals. While increased formal interactions have facilitated economic and social interaction, the utility of strategic partnerships has instruments of influencing Chinese behaviour in the international system remain minimal.